2015
DOI: 10.1016/j.breast.2015.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Breast conservative surgery and local recurrence

Abstract: Five defined oncoplastic principles presented in our nomogramme (targeted breast surgery) allow the reconstruction of major segmental resection defects during breast-conserving therapy with high clinical applicability and result in favorable oncological and aesthetic outcome. Recurrence was not a function of traditional prognostic factors like T-size or nodal status (in a T1/T2, N0/N1 cohort), but of grading, intrinsic subtypes and non-invasive breast cancer components. Lobular histology, multi-centricity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 54 publications
0
12
0
5
Order By: Relevance
“…The authors commented that most studies showed significant weaknesses including lack of robust design and methodological shortcomings. Well-designed prospective longitudinal studies with adequate follow-up are the only realistic way in which critics, who remain unconvinced by the existing data over three decades of oncoplastic surgery may be silenced (35)(36)(37)(38)(39).…”
Section: Resultsmentioning
confidence: 99%
“…The authors commented that most studies showed significant weaknesses including lack of robust design and methodological shortcomings. Well-designed prospective longitudinal studies with adequate follow-up are the only realistic way in which critics, who remain unconvinced by the existing data over three decades of oncoplastic surgery may be silenced (35)(36)(37)(38)(39).…”
Section: Resultsmentioning
confidence: 99%
“…This may be related to novel approaches in OBS. Oncologic outcomes on OBS have been evaluated, with the risk of recurrence not being attributed to surgical technique or resected volume [3]. However, if positive margins are documented, these techniques (if tissue rearrangement and remodeling occurs) may difficult further margin resection [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…However, with the new concepts of tumor biology, the determining factors are currently more related to the molecular biology of the tumor and adjuvant therapy than with the size of the resection margin. Such concept was popularized as "bigger is not better" 13,14 . Factors such as histological degree, components of noninvasive carcinoma, lobular histology, and multicentricity are predictive of conservative surgery failure and conversion to mastectomy 14 .…”
Section: Local Recurrence and Re-operating Ratementioning
confidence: 99%
“…Such concept was popularized as "bigger is not better" 13,14 . Factors such as histological degree, components of noninvasive carcinoma, lobular histology, and multicentricity are predictive of conservative surgery failure and conversion to mastectomy 14 . There are countless risk factors associated with a high rate of new surgeries due to compromised margins.…”
Section: Local Recurrence and Re-operating Ratementioning
confidence: 99%
See 1 more Smart Citation